Implications of Using Artificial Intelligence Chatbot in Fiqh Learning at Islamic Universities - Abdul Rahman Ramadhan (UIN Sulthan Thaha Saifuddin Jambi, 2025)
The rapid advancement of artificial intelligence (AI) has transformed various sectors, including education. This research explores the implications of AI chatbot utilization in fiqh learning at Islamic universities, analyzing its benefits, challenges, and ethical considerations. Employing a qualitative descriptive approach, data were collected through observations and closed-ended questionnaires distributed to lecturers and students from three Islamic universities: Sekolah Tinggi Dirasat Islamiyah Imam Syafi’i Jember, Safwa University Egypt, and International Quran University Gambia. The findings indicate that AI chatbots, particularly ChatGPT, are widely adopted among students (59%), while lecturers' usage remains relatively low (14%). This research reveals that AI chatbots enhance accessibility, engagement, and understanding of fiqh concepts, with 74% of respondents considering the responses accurate. However, concerns arise regarding misinformation, ethical accountability, and the risk of diminishing human interaction in religious learning. Despite their advantages, AI chatbots require continuous improvement to align with Islamic teachings and maintain scholarly rigor. This research recommends a balanced integration of AI chatbot technology with traditional fiqh instruction to ensure the depth and accuracy of religious education while addressing ethical and pedagogical challenges.